Protecting working-age people with disabilities: experiences of four industrialized nations - Richard V. Burkhauser; Mary C. Daly; Nicolas Ziebarth (Journal for Labour Market Research, 2016)
Although industrialized nations have long provided public protection to working-age individuals with disabilities, the form has changed over time. The impetus for change has been multi-faceted: rapid growth in program costs; greater awareness that people with impairments are able and willing to work; and increased recognition that protecting the economic security of people with disabilities might best be done by keeping them in the labor market. Here we describe the evolution of disability programs in four countries: Germany, the Netherlands, Sweden, and the United States. We show how growth in the receipt of publically provided disability benefits has fluctuated over time and discuss how policy choices played a role. Based on our descriptive comparative analysis we summarize shared experiences that potentially benefit policymakers in all countries.
Keywords: I10; I13; J14; J18; 330; Behinderte; Behindertenpolitik - internationaler Vergleich; Beschäftigungspolitik; berufliche Integration; Arbeitsförderung; Reformpolitik; politischer Wandel; Erwerbsunfähigkeitsrente; Erwerbsminderungsrente; Rentenpolitik; Bundesrepublik Deutschland; Niederlande; Schweden; USA